A Clinical Study of Drakshadi Syrup in Lowering Absolute Eosinophil Count (AEC) and Immunoglobulin E(Ige) Level in Tamak Swash (Bronchial Asthma) in Children (International Journal of Ayurveda and Pharma Research, 2024)
Childhood asthma is a prevalent chronic disease worldwide, affecting millions of children. Its impact is not only on the children themselves but also on their families, schools, and healthcare systems. Inspite of all recent advances in modern medical science the prevalence is increasing day by day. Aim: The present study is to assess the response of polyherbal compound ‘Drakshadi Syrup’ in lowering AEC and IgE level in childhood bronchial asthma. Materials and Methods: 106 nos. of patient were registered irrespective of sex between the age group 3-16 years out of which 100 patients completed the trial. Routine blood investigations including basic pathological markers i.e., AEC and IgE were recorded before and after 90 days of treatment. Statistical Tool Used: Paired-t test was done in GraphPad prism 10 software for data analysis. Results and Conclusion: After statistical analysis the t value of AEC was 13.31 with p